Ulam-Hyers-Rassias Stability for Semilinear Equations - Wang, Jinrong; Fečkan, Michal (Discontinuity, Nonlinearity, and Complexity, 2026)
We study the Ulam-Hyers-Rassias stability for linear and semilinear equations on Banach spaces from a functional analysis point of view with several illustrative examples. More precisely, surjective linear equations on Banach spaces, linear equations on Banach spaces with closed ranges and surjective semilinear equations between Banach spaces are investigated one by one.